Treatment of feline pyothorax: A report of two spontaneous cases - KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; PRASSINOS (Ν.Ν. ΠΡΑΣΙΝΟΣ), N. N.; ADAMAMA-MORAITOU (Κ.Κ. ΑΔΑΜΑΜΑ-ΜΩΡΑΪΤΟΥ), K. K.; KRITSEPI (Μ.Γ. ΚΡΙΤΣΕΠΗ), M. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Two cases of feline pyothorax, presented in severe respiratory distress, were treated successfully by applying intermittent drainage and daily lavage of the pleural space with warm normal saline. Before that an indwelling thoracostomy tube had been fixed on the thoracic wall and left in place from 5 to 10 days. The only complication noticed was a symptomatic pneumothorax due to either tube malpositioning or damage to the tube wall. In both instances, the inspiratory dyspnea decreased or disappeared as soon as the tube was removed. Systemic and long term (6-9 weeks) treatment with antibiotics, combined with supportive measures and good nursing care, had a positive effect to the successful outcome in both cases.